Do as I Say, Not as I Did: How Parents Talk With Early Adolescents About Sex. (January 2016) - Grossman, Jennifer M.; Charmaraman, Linda; Erkut, Sumru
Communication between parents and teens about sexuality can reduce early sexual behavior. However, little research investigates how parents who were adolescents when they had children (early parents) talk with their teens about sex. In-depth interviews were conducted with a racially/ethnically diverse sample of 29 parents of seventh graders. Salient themes of conversations with adolescents were risks of early parenthood, sexually transmitted infections, delaying sex, and using protection. Compared with parents who were older when they had children (later parents), early parents were more likely to report having had negative sexuality communications with their families of origin and to express a wish to communicate differently with their own children. Early parents were more likely than later parents to discuss risks of early parenthood and to rely on extended family involvement in sexuality communication. Findings suggest that early parents may bring unique perspectives that enable them to approach sexuality communication differently than do later parents.